MEDIA SOSIAL DAN PENGARUHNYA TERHADAP PARTISIPASI PEMILIH PEMULA DI PILKADA 2024 ACEH TENGGARA - Mustapa Kamil Alga Beruh; Lusiana Lusiana (ADMIN: Jurnal Administrasi Negara, 2024)
Regional head elections are a process of replacing regional heads, which is a democratic process that produces future leaders, but in the process sometimes it has a positive or negative impact. The influence of modernization makes the people of Southeast Aceh more mature in democracy, social media which is a mouthpiece for information to the public will have a very significant influence on thinking, especially among young people or new voters. Where new voters are a vote bank that is quite decisive in the regional head election in Southeast Aceh 2024. However, on the contrary, young people are often the target of those who spread false information, so they are vulnerable to being objects by the perpetrators of the hoax spreaders. KIP Aceh Tenggra as the organizer is of course an institution that has the authority to carry out a series of regional head election activities using social media as a dissemination of information at every stage of the regional election, namely Facebook as a social media that often makes people get every stage of the 2024 regional head election. Also, each candidate uses social media in the process of socializing an effective vision and mission to reach new voters in Southeast Aceh. However, it is not uncommon for sympathizers to use Facebook as a medium to spread incorrect information to attack their opponents in the 2024 Southeast Aceh district elections. It is very unfortunate if this can worsen Indonesian democracy in the future.